Spillover effects of the COVID-19 pandemic on attitudes to influenza and childhood vaccines - Soveri Anna; Karlsson Linda C.; Antfolk Jan; Mäki Otto; Karlsson Linnea; Karlsson Hasse; Nolvi Saara; Karukivi Max; Lindfelt Mikael; Lewandowsky Stephan (BioMed Central Ltd, 2025)
The current study sought to determine whether public perceptions of other vaccines and diseases than COVID-19 have been impacted by the COVID-19 pandemic. We longitudinally examined whether there had been a change from before the COVID-19 pandemic to during the pandemic in: (a) influenza vaccination behaviour and intentions; (b) the perceived benefit of childhood vaccines and influenza vaccines; (c) the perceived safety of childhood vaccines and influenza vaccines; (d) the perceived severity of measles and influenza; and (e) trust in healthcare professionals in two samples of Finnish adults (N = 205 in Study 1 and N = 197 in Study 2). The findings showed that during the pandemic, more people than before had received or wanted to receive the influenza vaccine. The respondents also believed that influenza was more dangerous during the pandemic and that vaccinations were safer and more beneficial. On the other hand, for childhood vaccines only perceived safety increased. Finally, in one of the studies, people had more confidence in medical professionals during the pandemic than they had before. Together, these findings imply a spillover of the COVID-19 pandemic on how people view other vaccines and illnesses. © 2023, The Author(s).